2007
DOI: 10.1371/journal.pone.0001155
|View full text |Cite
|
Sign up to set email alerts
|

Common Activation of Canonical Wnt Signaling in Pancreatic Adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDA) is an extremely aggressive malignancy, which carries a dismal prognosis. Activating mutations of the Kras gene are common to the vast majority of human PDA. In addition, recent studies have demonstrated that embryonic signaling pathway such as Hedgehog and Notch are inappropriately upregulated in this disease. The role of another embryonic signaling pathway, namely the canonical Wnt cascade, is still controversial. Here, we use gene array analysis as a platform to demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
165
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(184 citation statements)
references
References 47 publications
18
165
1
Order By: Relevance
“…The potent soluble activators of FZD3/6/7 are very likely those ligands to be found overexpressed in HCCs (WNT3/4/5A). These data correlate with FZD3/6 and WNT3 found overexpressed in other malignancies as leukaemia, FZD7 in solid tumours like nasopharynx, oesophagus, and stomach carcinomas, WNT5A in leukaemia, melanoma, and nasopharynx carcinoma (Tanaka et al, 1998;Kirikoshi et al, 2001;Holcombe et al, 2002;Weeraratna et al, 2002;Qiang et al, 2003;Lu et al, 2004;Zeng ZY et al, 2007), whereas WNT4 has been previously found overexpressed in pancreatic cancers (Pasca di Magliano et al, 2007). Concerning the soluble activators of FZD, previous studies have shown the common downregulation of sFRP1 due to promoter hypermethylation in HCC as well as in colon cancer (Suzuki et al, 2004;Shih et al, 2006Shih et al, , 2007.…”
Section: Discussionsupporting
confidence: 82%
“…The potent soluble activators of FZD3/6/7 are very likely those ligands to be found overexpressed in HCCs (WNT3/4/5A). These data correlate with FZD3/6 and WNT3 found overexpressed in other malignancies as leukaemia, FZD7 in solid tumours like nasopharynx, oesophagus, and stomach carcinomas, WNT5A in leukaemia, melanoma, and nasopharynx carcinoma (Tanaka et al, 1998;Kirikoshi et al, 2001;Holcombe et al, 2002;Weeraratna et al, 2002;Qiang et al, 2003;Lu et al, 2004;Zeng ZY et al, 2007), whereas WNT4 has been previously found overexpressed in pancreatic cancers (Pasca di Magliano et al, 2007). Concerning the soluble activators of FZD, previous studies have shown the common downregulation of sFRP1 due to promoter hypermethylation in HCC as well as in colon cancer (Suzuki et al, 2004;Shih et al, 2006Shih et al, , 2007.…”
Section: Discussionsupporting
confidence: 82%
“…Activation of the Wnt target gene will contribute to the development of cancer in terms of proliferation, invasion and metastasis, and angiogenesis (Taketo, 2006;Neth et al, 2007). Additionally, inhibition of Wnt signalling could reduce cell proliferation and increase apoptosis in pancreatic adenocarcinoma cells (Miao et al, 2003;Pasca di Magliano et al, 2007;Nawroth et al, 2007). Here, the b-catenin/Tcf assay showed that the TOPflash luciferase activity was obviously decreased whereas FOPflash luciferase activity has no change.…”
Section: Discussionmentioning
confidence: 91%
“…The effect of the Wnt down-regulation was a reduction of cell proliferation [Pasca di Magliano et al, 2007] and an induction of terminal cell differentiation [Boyden et al, 2002;van der Horst et al, 2005]. Many Wnt effects are mediated through β-catenin, which accumulates in the cytoplasm and translocates to the nucleus if the Wnt pathway is activated.…”
Section: Discussionmentioning
confidence: 99%